The Effectiveness of Person-Organization Fit Training on Increasing Work Engagement For Employee at Rehabilitation Center (Badan Narkotika Nasional) - Alfina, Irma; Secapramana, Laurentia Verina Halim (Fathana, 2026)
This study examined the effectiveness of a Person–Organization Fit (P–O Fit)-based soft skills training on work engagement using a true experimental pretest–posttest control group design. A total of 40 rehabilitation-implementing employees were randomly assigned to an experimental group (n = 20) or a control group (n = 20). The experimental group received a structured P–O Fit training intervention, while the control group received no treatment. Work engagement was measured before and after the intervention using the Utrecht Work Engagement Scale (UWES). Group differences were analysed using inferential statistical techniques. The results indicated no statistically significant difference in work engagement between the experimental and control groups at posttest (p = 0.935). However, categorical analysis revealed changes in the experimental group's participants' levels of attitude.